Identification and Potential of Wood-Decaying Fungi from Poteran Island as a Source of Manganese Peroxidase (MnP) - Putri, Arum Maulinda; Kuswytasari, Nengah Dwianita; Prasetyo, Endry Nugroho (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Poteran Island is among the largest islands located within the Sumenep Regency, characterized by lowland agricultural areas with a dry E5 climate, allowing only one planting cycle of secondary crops per year. However, during the rainy season, the region tends to experience an abundance of wood-decaying fungi. This study aims to identify and evaluate the potential of wood-decaying fungi from Poteran Island as a source of MnP using morphological approaches. Screening of MnP-producing fungal isolates was carried out on L-MSM medium supplemented with methylene blue, and the clear zones were observed. The isolates were then identified macroscopically on petri dishes and microscopically using Lactophenol cotton blue, with reference to the book Pictorial Atlas of Soil and Seed Fungi: Morphologies of Cultured Fungi and Key to Species. Based on the morphological examination of 20 fungal isolates, 11 isolates displayed white mycelium, 1 isolate had gray mycelium, 2 isolates showed greenish-white mycelium, and 2 isolates had yellowish-white mycelium. Furthermore, 14 isolates exhibited circular colony morphology, 3 isolates were semi-circular, and 3 isolates were filamentous (filiform) in shape. MnP-producing fungal isolates were screened using L-MSM medium supplemented with methylene blue. Only one isolate, DS 18, demonstrated MnP production potential, indicated by the decolorization of methylene blue on medium. Macroscopic and microscopic analyses confirmed that isolate DS 18 is Trametes versicolor, as it exhibited similar characteristics, including a cottony texture, white color, smooth colony edges, non-septate hyphae, elliptical spores, and hyphae with clamp connections.